Composite orbital reconstruction using the vascularized segmentalized osteo-fascio-cutaneous fibula flap. Issue 2 (February 2016) - Lundgren, T. Kalle; Pignatti, Marco; Halle, Martin; Boscaini, Giulia; Docherty Skogh, Ann-Charlotte; Luigi, Chiarini; De Santis, Giorgio
Summary: Reconstruction of composite orbital defects must address the orbit and an exposed skull base and/or maxillary region. The orbit should not only be covered but also reshaped to accommodate the orbital contents or an epithesis when warranted. This study presents a rationale for a near-anatomical reconstruction of the orbit, together with adjacent dead space obliteration, using the segmentalized osteo-fascia-cutaneous fibula flap. Before the flap transfer, a cutting template for the fibula is made according to the measures and requirements of the facial defect. The segmentalized bone is then osteosynthesized to the facial skeleton and revascularized. Thus, an orbital depth is created by the bony fibula, whereas the fascio-cutaneous part of the flap may be used for lining the orbit and obliteration of the skull base or the maxillary region, or resurface the palate and/or the nasal cavity.